Variability of nuchal translucency measurement : A multicenter study in Thailand - SUNTHARASAJ, Thitima; RATANASIRI, Thawalwong; CHANPRAPAPH, Pharuhas; KENGPOL, Chitkasaem; KOR-ANANTAKUL, Ounjai; LEETANAPORN, Roengsak; PRASARTWANAKIT, Visit; KLEEBKAOW, Pilaiwan; TONGSONG, Theera; SIRICHOTIYAKUL, Supatra (Gynecologic and obstetric investigation, 2005)
To evaluate intra- and inter-observer variations of nuchal translucency (NT) measurements and study the duration of measurements. One hundred and forty-seven singleton pregnant women with 10-14 weeks of gestation who had attended antenatal clinic during January 1st, 2000-August 31st, 2001 were included. Crown-rump length and NT were measured three times for each woman. Then, another examiner who was unaware of the previous results did the other three measurements. The duration of measurements was recorded. Intra-observer and inter-observer variations were analyzed by repeated ANOVA and paired t test, respectively. The correlation of NT measurements within each observer and between paired observers was evaluated by intraclass correlation coefficients (ICC). Kappa statistic was calculated for agreement. Intra-observer variation of all 10 examiners at three institutes was varied from 0.20 +/- 0.27 to 0.33 +/- 0.41 mm. Inter-observer variation at Chiang Mai University was 0.40 +/- 0.37 mm which was the highest value compared with those at Prince of Songkla and Khon Kaen University (p < 0.05). The mean duration of measurements was in range of 8-12 min. The intra-observer repeatability of the first two measurements showed ICCs varying from 0.61 to 0.94. The inter-observer repeatability of paired examiners showed a variation in ICC from 0.28-0.90. The kappa value expressing the intra- and inter-observer repeatability as being >95th or < or = 95th percentile was 0.73 and 0.72, respectively. NT measurement was reproducible for small variation and good agreement. The duration of measurements was acceptable.